Network pharmacology-based analysis of Resinacein S against non-alcoholic fatty liver disease by modulating lipid metabolism - Mao, Fei-Fei; Gao, Shan-Shan; Huang, Yan-Jie; Zhou, Nian; Feng, Jin-Kai; Liu, Zong-Han; Zhang, Yu-Qing; Yuan, Lu-Yun; Wei, Gang; Cheng, Shu-Qun (Frontiers in Nutrition, 2023)
Ganoderma lucidum is reportedly the best source of traditional natural bioactive constituents. Ganoderma triterpenoids (GTs) have been verified as an alternative adjuvant for treating leukemia, cancer, hepatitis and diabetes. One of the major triterpenoids, Resinacein S, has been found to regulate lipid metabolism and mitochondrial biogenesis. Nonalcoholic fatty liver disease (NAFLD) is a common chronic liver disease that has become a major public health problem. Given the regulatory effects on lipid metabolism of Resinacein S, we sought to explore potential protective effects against NAFLD. Our results can be summarized as follows: (1) The structure of Resinacein S was elucidated using NMR and MS methods. (2) Resinacein S treatment could significantly attenuate high-fat diet (HFD)-induced hepatic steatosis and hepatic lipid accumulation in mouse. (3) GO terms, KEGG pathways and the PPI network of Resinacein S induced Differentially Expressed Genes (DEGs) demonstrated the key target genes of Resinacein S against NAFLD. (4) The hub proteins in PPI network analysis could be used for NAFLD diagnosis and treatment as drug targets.